2002
DOI: 10.1182/blood.v99.2.499
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of transforming growth factor β–mediated cell-cycle modulation in primary human CD34+ progenitors

Abstract: The mechanisms by which transforming growth factor ␤ (TGF-␤) exerts a negative effect on cell-cycle entry in primary human hematopoietic stem/progenitor cells were examined at the molecular and cellular levels. After treatment of primary human CD34 ؉ progenitors with TGF-␤ there was a decrease in the levels of cyclin D2 protein and an increase in levels of the cyclin-dependent kinase inhibitor (CDKI) p15 as compared to the levels in un-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…In addition, we found that Myc/ ERT efficiently induced the expression of cyclin D2, cyclin D3, and cyclin E and promoted the growth of HSCs. In addition, previous reports suggested that c-Myc would transcriptionally repress the expression of p21 WAF1 , which plays a crucial role in the quiescence of HSCs (19,51), and of p15 INK4b , which is induced by transforming growth factor-␤ signaling (52,53). Together, these results imply that the c-myc could be a master regulator of the cell cycle in both Notch1-and HOXB4-induced self-renewal of HSCs.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, we found that Myc/ ERT efficiently induced the expression of cyclin D2, cyclin D3, and cyclin E and promoted the growth of HSCs. In addition, previous reports suggested that c-Myc would transcriptionally repress the expression of p21 WAF1 , which plays a crucial role in the quiescence of HSCs (19,51), and of p15 INK4b , which is induced by transforming growth factor-␤ signaling (52,53). Together, these results imply that the c-myc could be a master regulator of the cell cycle in both Notch1-and HOXB4-induced self-renewal of HSCs.…”
Section: Discussionsupporting
confidence: 55%
“…CDKIs that are often seen to be up-regulated by TGF␤ in epithelial and neural progenitor cells (e.g., p15, p27, and p21) are not immediate targets of this cytokine in hematopoietic cells, and neither p21 nor p27 is necessary for TGF␤ to affect cytostasis in immature hematopoietic cells (8,34,35). p15 does not appear to be an early target of TGF␤ in CB-CD34ϩ cells (or in the M091 cells at any time), suggesting that the delayed up-regulation of p15 sometimes seen in these cells in response to TGF␤ (36,37) is a consequence of earlier events. The strong TGF␤-mediated up-regulation of p57 that we observed in immature human hematopoietic cells is not seen in many epithelial cell types (18), further demonstrating that critical aspects of TGF␤-signaling are cell type specific.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Several studies have implicated that TGF-b may act through mechanisms involving the cip/kip inhibitors of CDKs (p21 Cip1 / p27 Kip1 ). [49][50][51] However, there is also data supporting a model whereby TGF-b can exert growth arrest independent of this class of cell cycle regulators. 52 It is also known that TGF-b can directly control the expression of the stem cell antigen CD34, 53,54 and in specific contexts, can prohibit differentiation via mechanisms not linked to cell cycle arrest.…”
Section: Ink4bmentioning
confidence: 99%